Improvement of precision in refinements of structure factors using convergent‐beam electron diffraction patterns taken at Bragg‐excited conditions. Issue 4 (14th June 2021) - Aryal, B.; Morikawa, D.; Tsuda, K.; Terauchi, M.
Abstract : A new strategy for improving precision and sensitivity in the refinement of crystal structure factors is proposed. This technique will help to precisely determine the chemical bonding states of crystalline materials, which are closely related to their physical properties. Abstract : A local structure analysis method based on convergent‐beam electron diffraction (CBED) has been used for refining isotropic atomic displacement parameters and five low‐order structure factors with sin gθ/λ ≤ 0.28 Å −1 of potassium tantalate (KTaO3 ). Comparison between structure factors determined from CBED patterns taken at the zone‐axis (ZA) and Bragg‐excited conditions is made in order to discuss their precision and sensitivities. Bragg‐excited CBED patterns showed higher precision in the refinement of structure factors than ZA patterns. Consistency between higher precision and sensitivity of the Bragg‐excited CBED patterns has been found only for structure factors of the outer zeroth‐order Laue‐zone reflections with larger reciprocal‐lattice vectors. Correlation coefficients among the refined structure factors in the refinement of Bragg‐excited patterns are smaller than those of the ZA ones. Such smaller correlation coefficients lead to higher precision in the refinement of structure factors.